FAKTOR – FAKTOR YANG MEMPENGARUHI GENERASI Z DALAM KEPUTUSAN MENGGUNAKAN LAYANAN E-MONEY PADA MAHASISWA FAKULTAS EKONOMI DAN BISNIS ISLAM UIN SULTHAN THAHA SAIFUDDIN JAMBI (Lembaga Pengembangan Kinerja Dosen, 2023)
This Study aims to analyze the effect of perceptions of trust and perceived risk on the use of e-money services on students of the Faculty of Islamic Economics and Business UIN Sulthan Thaha Saifuddin Jambi. The method used in this research is a quantitative method. The population in this study amounted to 96 students. Collecting data in this thesis through observation, interviews and questionnaires. The results of this study indicate that the perceived trust variable has a significant positive effect on the use of e-money services. Furthermore, the variable perceptions of trust and perceived risk together have a significant effect on the variable of using e-money services. This illustrates that the contribution of the independent variable to the dependent variable has a effect of 67,9% and the remaining 32,1% is influenced by other variables not examined in this study. So it can be concluded that if the variable perceptions of trust and perceived risk experience an increase, then the variable use of e-money services of students of the Islamic economics and business faculties of UIN Sulthan Thaha Saifuddin Jambi will also experience an increase.